Rationales, design and recruitment of the Taizhou Longitudinal Study - Lu Daru; Li Shilin; Yang Yajun; Qian Ji; Lu Ming; Wang Xiaofeng; Yu Shunzhang; Meng Wei; Ye Weimin; Jin Li (BMC, 2009)
Background Rapid economic growth in China in the past decades has been accompanied by dramatic changes in lifestyle and environmental exposures. The burdens of non-communicable diseases, such as cardiovascular diseases, diabetes and cancer, have also increased substantially. Methods/design We initiated a large prospective cohort-the Taizhou Longitudinal Study-in Taizhou (a medium-size city in China) to explore the environmental and genetic risk factors for common non-communicable diseases. The sample size of the cohort will be at least 100,000 adults aged 30-80 years drawn from the general residents of the districts of Hailin, Gaogang, and Taixing (sample frame, 1.8 million) of Taizhou. A three-stage stratified sampling method will be applied. Baseline investigations include interviewer-administered questionnaire, anthropometric measurements, and collection of buccal mucosal cells and blood specimens. DNA will be extracted for genetic studies and serum samples will be used for biochemical examinations. A follow-up survey will be conducted every three years to obtain information on disease occurrence and information on selected lifestyle exposures. Study participants will be followed-up indefinitely by using a chronic disease register system for morbidity and cause-specific mortality. Information on non-fatal events will be obtained for certain major categories of disease (e.g., cancer, stroke, myocardial infarction) through established registry systems. Discussion The Taizhou Longitudinal Study will provide a good basis for exploring the roles of many important environmental factors (especially those concomitant with the economic transformation in China) for common chronic diseases, solely or via interaction with genetic factors.